Multiple Nonsyndromic Unerupted Supernumerary Teeth: A Report of a Rare Case - Mehrnaz Moradinejad; Alireza Hashemi Ashtiani; Vahid Rakhshan (Hindawi Limited, 2022)
Introduction. The prevalence of nonsyndromic multiple supernumerary teeth is less than 1% of all hyperdontia cases which themselves have a rather small prevalence. Cases with 10 impacted nonsyndromic supernumerary teeth are extremely rare. This report presents such a case of nonsyndromic multiple impacted supernumerary teeth. Case. A 17-year-old boy with a completely orthodontic chief complaint attended our center. He had no systemic complaints and no signs or symptoms. Oral examination showed no abnormalities. On routine pretreatment panoramic radiography, numerous impacted supernumerary teeth appeared. A CBCT showed 10 impacted vertically aligned supplementary supernumerary teeth with incomplete roots: In the maxilla, the bilateral canine-premolar areas were involved, each having 2 supernumerary teeth palatal to the permanent teeth. In the mandible, the right premolar area included 2 supernumerary teeth. The left premolar-molar area contained 3 supernumerary teeth lingual to the permanent teeth. And in the right mandibular molar area, there was a distomolar tooth distal to the third molar. No bony ankyloses, root resorptions, or fusions were observed. The surrounding bone had become thinner and the mandibular alveolar canal was involved. Interventions. All supernumerary teeth except a mandibular distomolar were extracted carefully before beginning the orthodontic treatment. No complications were seen after the extraction, after orthodontic treatment, and 2 years after treatment. Conclusions. The possibility of completely hidden unerupted supernumerary teeth without any signs and symptoms might highlight the value of some radiographic screenings.